Soluble human macrophage factors are able to inhibit TGF-β-induced differentiation of lung fibroblasts - A. A. Maksimova; E. Ya. Shevela; L. V. Sakhno (Медицинская иммунология)
Macrophages are key regulatory cells of fibrogenesis. They can have pro- or antifibrotic activity due to their plasticity and heterogeneity. Some studies have shown the antifibrotic effect of macrophages on dermal fibroblasts, but the effect of macrophages on the lung fibroblast functions remains unexplored. Therefore, the purpose of this study was to examine the influence of conditioned media of human macrophage differentiated by M-CSF/GM-CSF and further dexamethasone polarized/unpolarized on the TGF-β-induced lung fibroblast differentiation. Macrophages were derived from peripheral blood monocytes of healthy donors. Monocytes were differentiated by M-CSF or GM-CSF for 7 days. On day 5, dexamethasone was added to generation of polarized macrophages M-M(Dex) and GM-M(Dex). Polarized macrophages were compared with non-polarized M-M0 and GM-M0, to which dexamethasone was not added. Next, the conditioned medium of these macrophage subtypes was collected and tested for inhibition the lung fibroblast differentiation (HLF210 cell line). To do this, TGF-β (inducing differentiation factor) and conditioned macrophage medium were added to fibroblast cultures. Effectiveness of differentiation was estimated by the expression of the myofibroblast marker, α-smooth muscle actin (α-SMA), and the production of extracellular matrix protein, collagen I. The expression of α-SMA was determined using flow cytometry. The concentration of collagen I was measured by ELISA. Since our data indicates that spontaneous activation of fibroblasts occurs during standard cultivation, the α-SMA expression was investigated in 3D culture of fibroblasts. Notably, the content of α-SMA-positive cells in 3D cultures was significantly reduced, indicating more physiological growth cells. Regardless of the differentiation stimulus, the conditioned media of dexamethasone-polarized macrophages do not affect the level of collagen I production or the α-SMA expression. On the contrary, M-M0 showed a strong inhibitory effect that reduced the amount of collagen I in the fibroblast cultures and the expression of marker myofibroblasts by fibroblasts. Interesting, GM-M0 had no such effect and did not prevent lung fibroblast differentiation like polarized cells. Taken together, the findings suggest that M-M0 macrophages may have antifibrotic properties. Furthermore, the lack of this effect in GM-M0 macrophages indicates that the differentiation factor plays a significant role in the development of the antifibrotic macrophage phenotype.